iASPP regulates neurite development by interacting with Spectrin proteins - Wang, Junhao; Jia, Chunhong; Gao, Qiong; Zhang, Jiwen; Gu, Xi (Frontiers in Molecular Neuroscience, 2023)
Since its discovery in 1999, a substantial body of research has shown that iASPP is highly expressed in various kinds of tumors, interacts with p53, and promotes cancer cell survival by antagonizing the apoptotic activity of p53. In this study, we found that the expression of iASPP gradually decreased during neuronal development. iASPP silencing promotes neuronal differentiation, while its overexpression inhibited neurite differentiation in a variety of neuronal differentiation cellular models. iASPP associated with the cytoskeleton-related protein Sptan1 and dephosphorylated the serine residues in the last spectrin repeat domain of Sptan1 by recruiting PP1. The non-phosphorylated and phosphomimetic mutant form of Sptbn1 inhibited and promoted neuronal cell development respectively. Overall, we demonstrate that iASPP suppressed neurite development by inhibiting phosphorylation of Sptbn1.